If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 9 + 2x Reorder the terms: -5 + 4x = 9 + 2x Solving -5 + 4x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 4x + -2x = 9 + 2x + -2x Combine like terms: 4x + -2x = 2x -5 + 2x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 2x = 9 + 0 -5 + 2x = 9 Add '5' to each side of the equation. -5 + 5 + 2x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 9 + 5 2x = 9 + 5 Combine like terms: 9 + 5 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 7-5x+7x=15 | | 8y^2-1y-9=0 | | 11+m=-1 | | 2+4/3+5 | | -21=-7(3+6a) | | 2X-2(2-X)=40 | | 2+264-120h=8h+112-102h | | -9+3x+6x=-117 | | 4t+1/5=1(3/10) | | 5(c-24)=5 | | 4t+1/5=1 | | 4t+1/5=13/10 | | 8m-2=-9+7m | | 6=p+(-10) | | 2t^2-1t-6=0 | | 1/2f+4/7 | | -80=5x+5x-10 | | -15n+k=8 | | 2=4x+6x+2 | | 10(d-4)= | | -10+7n=8[5+4n] | | [2x-4]=22 | | 5z-4y+6-3y-z= | | 5-6x+3x=14 | | 2(m-16)=4 | | 8w-56=-72 | | 3/5t-2+7 | | 3x-8+x=20 | | 8x-7=6x-9 | | 8+4x=-8+2x | | 11-5(v+8)=-(9v-3) | | 15-5v=-(2v-6) |